For A Cause (FAC), An NGO Contributing to the Society-A Case Study on Transformation of Undergraduate Students Through Community Engagement - A, Suresh; SV, Devika; S, Arvind; K, Bindu Madhavi; K, Aasrith; G, Hemanth; Siva, Deekshith (Journal of Engineering Education Transformations, 2025)
A Case study on Societal contribution done in Hyderabad Institute of Technology and Management (HITAM), Hyderabad is presented in the paper. As the vision of the Institute clearly emphasizes on contribution to the society, HITAM students initiated an NGO “FOR A CAUSE (FAC)”, A Non-Governmental Organization (NGO) in the year 2017. The objective of this NGO is to feed and help needy by providing technical solutions to their problems and extend their support to the poor. Initially it was started as a club then it got recognised by the Government as an NGO. The curriculum of the Institution is designed in such a way that there are few courses where students would get motivated and encouraged to work and contribute to society in various ways. A team of students from multiple disciplines join their hands and identify societal needs. The team provides the technical solutions through their Engineering knowledge. This community engagement activities created an impact on undergraduate students’ thinking towards society. Students learnt project management and critical analysis through these activities. This also helps in the holistic development of the students.